Ki Rinyuh (Chromolaena odorata (L) R.M. King and H. Robinson): The Harmful Pastureâs Weed - Prawiradiputra, Bambang R (Indonesian Animal Sciences Society, 2007)
Ki rinyuh (Chromolaena odorata (L) R.M. King and H. Robinson) is one of the important weeds in Indonesia. Originally from Central America, but now the weed spreads out tropical and sub-tropical countries. The weed is well grown in any kind of soil. The harmful effect of C. odorata on livestock in Indonesia first reported in 1971. They are four reasons to put this species as detrimental weed: (1) decreases carrying capacity, (2) poisons or probably causes death of livestock, (3) competitor with grasses or legumes Â crops, Â and Â (4) Â fire Â hazard Â especially Â in Â the Â dry seasons. Â Herbicides Â control Â isÂ not Â effective Â and Â it Â is Â not environmentally friendly. Other ways of controlling this weed are by slashing and biological control. Controlling C. odorata by combination of slashing and herbicides would be more effective than using herbicides only. The weed can be utilized as fertilizer or growth regulator to improve plant morphology and to increase the yield of some plants. Â Key words: Chromolaena odorata, weed, pasture, control, benefit